Dothan I Remains from the Tell (1953-1964) - Barkay, Gabriel; Eger, A. Asa; Johnston, Philip; Keimer, Kyle H.; Larsen, Timothy; Lass, Egon H. E.; Master, Daniel M.; Master, Daniel M.; Monson, John M.; Monson, John M.; Pierce, George A.; Pierce, George A.; et al. (Penn State University Press, 2021)
The city of Dothan appears both in the Joseph narratives (Genesis 37) and as the city to which Elisha the prophet fled from the Arameans-and where the king of the Arameans sent an army to attempt to retrieve him (2 Kings 6:13). In the late 1950s and early 1960s, excavations at the site were sponsored by Wheaton College (Illinois), with Joseph P. Free as Director. This first volume publishes the results of those excavations and will be welcomed by all who wish to study the material at greater length.Chapters on the history of the expedition, methodology, Early Bronze Age and Late Bronze Age, the Iron Age, the Hellenistic, Roman, and Byzantine eras are complemented by studies on stone and metal artifacts, Iron II seal impressions, and Rhodian stamp seal impressions. The volume is profusely illustrated, with more than 200 photos and drawings and 2 color plates.Volume 2 of the series will report on the Western Cemetery at Dothan, which was the source of a rich repertoire of Late Bronze Age pottery